Psychoneuroimmunoendocrinology: clinical implications - Sandra Nora González-Díaz; Alfredo Arias-Cruz; Bárbara Elizondo-Villarreal; Olga Patricia Monge-Ortega (World Allergy Organization Journal, 2017)
Abstract Psychoneuroimmunoendocrinology, which was first described in 1936, is the study of the interactions between the psyche, neural and endocrine functions and immune responses. The aim of psychoneuroimmunoendocrinology is to apply medical knowledge to the treatment of different allergic, immune, autoimmune, rheumatic, neoplastic, endocrine, cardiovascular and dental pathologies, among other disorders. Epigenetic factors and major stresses from different types of stimuli acting through distinct pathways and neurotransmitters are highly involved in altering the psychoneuroimmunoendocrine axis, resulting in the emergence of disease. The main purpose of this report is to expand the understanding of psychoneuroimmunoendocrinology and to demonstrate the importance of the above-mentioned interactions in the etiology of multiple pathologies. In this review, a search of the medical literature using PubMed (free access search engine for the Medline database of the National Library of Medicine of the United States) over the years 1936 to 2016 was conducted, and descriptive and experimental studies and reviews of the scientific literature were included.